A Low Complexity Active Sensing and Inspection System for Monitoring of Moveable Radiation Environments. (27th March 2018) - Ding, Fei; Zhang, Dengyin; Wang, Wanping; Lei, Zhenzhong
Abstract : Due to the portable property of moveable radiation sources, the traditional monitoring method is becoming increasingly unsuitable and it is urgent to provide an effective and low-cost method. This paper presents an active monitoring scheme for moveable radiation environments, the in situ monitoring, including a radiation detection node, an infrared proximity node, and an alarm node; these three schemes communicate with each other through the ZigBee wireless network. An active monitoring mechanism which realizes the automatic judgment of radiation source inbound or outbound state is proposed, thereby automatically switching the data sampling mode under different working conditions, so as to reduce the energy consumption of nodes. Based on the mobile terminal client application to interact with the monitoring center, a collaborative management mode between enterprise users and the environmental protection department is realized. A testbed of a simple active sensing and inspection system is created to test its user interaction capabilities. Experimental results prove that the system schedule proposed can effectively detect and dynamically monitor the moveable radiation source. The system can be easily replicated and extended to more environmental monitoring network.